OPTIMALISASI NILAI TAMBAH JAMBU MELALUI DIVERSIFIKASI PRODUK OLAHAN DI DESA KEDUNGSOLO - Fitri Nur Latifah; Muhammad Farras Abiyyu; Fauziah Putri; Arya Kusuma Dewa (Jurnal Ikhtibar Nusantara, 2026)
Kedungsolo Village, Porong District, Sidoarjo Regency possesses abundant guava production; however, the commodity is predominantly marketed as fresh fruit, resulting in relatively low added value for local communities. This condition highlights the need for product diversification as a community empowerment strategy based on local resources. This community service program aimed to improve community knowledge and skills in processing guava into value-added products, namely guava jam and pickled guava. The program adopted an Asset-Based Community Development (ABCD) approach through participatory activities consisting of potential identification, socialization, hands-on training, product processing practices, and program evaluation. The target participants included community members and local farmers involved in guava production. The results demonstrated that participants successfully understood and practiced the production of guava jam and pickled guava independently. Furthermore, the program increased community awareness of the importance of product diversification in enhancing the economic value of agricultural commodities while reducing dependence on the sale of fresh fruit. The high level of community participation throughout the activities indicates that the program was well received and has the potential to be sustained. Overall, the program contributed to strengthening community capacity in utilizing local guava resources as an alternative strategy for promoting village-based economic development.